Posted the problem backwards

Geometry Level 3

A B C \triangle ABC has sides a , b , c a, b, c such that 1 a + c + 1 b + c = 3 a + b + c \frac{1}{a+c}+\frac{1}{b+c}=\frac{3}{a+b+c} . Find C \angle C

Clarification: a a is the side opposite to vertex A A , b b is the side opposite to vertex B B and c c is the side opposite to vertex C C as shown in the image above.

75 60 15 30

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Maximos Stratis
Jun 6, 2017

1 a + c + 1 b + c = 3 a + b + c \frac{1}{a+c}+\frac{1}{b+c}=\frac{3}{a+b+c}\Rightarrow
a + b + 2 c ( a + c ) ( b + c ) = 3 a + b + c \frac{a+b+2c}{(a+c)(b+c)}=\frac{3}{a+b+c}
After some tedious algebra, we conclude that :
a 2 + b 2 = a b + c 2 a^{2}+b^{2}=ab+c^{2}\Rightarrow
c 2 a 2 b 2 = a b c^{2}-a^{2}-b^{2}=-ab
From the cosine law we have:
c 2 = a 2 + b 2 2 a b cos C c^{2}=a^{2}+b^{2}-2ab\cos{C}\Rightarrow
c 2 a 2 b 2 = 2 a b cos C c^{2}-a^{2}-b^{2}=-2ab\cos{C}\Rightarrow
a b = 2 a b cos C -ab=-2ab\cos{C}\Rightarrow
cos C = 1 2 \cos{C}=\frac{1}{2}\Rightarrow
C = 60 \boxed{C=60}

Note: The trig-equation cos C = 1 2 \cos{C}=\frac{1}{2} has infinite roots but since 0 < C < 180 0<C<180 the only root is 60.

There's a much easier way to manipulate the given expression rather than directly multiplying it out:

1 a + c + 1 b + c = 3 a + b + c ( a + b + c ) ( 1 a + c + 1 b + c ) = 3 ( a + c ) + b a + c + ( b + c ) + a b + c = 3 1 + b a + c + 1 + a b + c = 3 b a + c + a b + c = 1 b ( b + c ) + a ( a + c ) = ( a + c ) ( b + c ) b 2 + b c + a 2 + a c = a b + a c + b c + c 2 c 2 = a 2 + b 2 a b . \begin{aligned} \dfrac{1}{a + c} + \dfrac{1}{b + c} &= \dfrac{3}{a + b + c} \\ (a + b + c) \left ( \dfrac{1}{a + c} + \dfrac{1}{b + c} \right ) &= 3 \\ \dfrac{(a + c) + b}{a + c} + \dfrac{(b + c) + a}{b + c} &= 3 \\ 1 + \dfrac{b}{a + c} + 1 + \dfrac{a}{b + c} &= 3 \\ \dfrac{b}{a + c} + \dfrac{a}{b + c} &= 1 \\ b(b + c) + a(a + c) &= (a + c)(b + c) \\ b^2 + bc + a^2 + ac &= ab + ac + bc + c^2 \\ c^2 &= a^2 + b^2 - ab. \end{aligned}

Then, we can apply Law of Cosines as you did in your solution.

Steven Yuan - 4 years ago

Nice one! That was what I was looking for

Sathvik Acharya - 4 years ago

Log in to reply

Thank you!

maximos stratis - 4 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...